Pendampingan Pembuatan Sistem Informasi Sekolah Berbasis Web di SDN 1 Montong Baan - Zamroni; Amri Muliawan Nur; Ida Wahidah; Azrul Hidayat; M. Wahyudi Rahmatul Qodri (Jurnal Teknologi Informasi untuk Masyarakat, 2025)
Effective school information management is one of the important aspects in improving the quality of educational services. However, at SDN 1 Montong Baan, the information management process is still done manually, such as through announcements on information boards or direct communication with students' parents. This has caused several obstacles, such as delayed information, data inaccuracies, and limited access for the community. To address these challenges, a web-based school information system was developed with the aim of improving the efficiency and accuracy of school information management. This system is equipped with key features, such as a home page, school profile page, school program page, news & activities page, school facilities page, school achievements page, and new student registration page. The development of this system uses the Waterfall method, which includes the stages of requirement, design, implementation, verification, and maintenance. The development process begins with needs identification, system design, system construction, and ends with training and system testing with teachers and school staff. The implementation results show that this system successfully facilitates information management in a faster, more accurate, and structured manner. Users such as teachers, school staff, and parents of students provided positive feedback regarding the ease of access and reliability of the system. The success of this implementation is expected to serve as a model for web-based school information management for other schools, especially in rural areas